Substrate thickness variation on the frequency response of microstrip antenna for mm-wave application - Bello Abdullahi Muhammad; Mohd Fadzil Ain; Mohd Nazri Mahmud; Mohd Zamir Pakhuruddin; Ahmadu Girgiri; Mohamad Faiz Mohamed Omar (Universitas Ahmad Dahlan, 2025)
Substrate height (Hs) is an important parameter that influences antenna propagation. This research designed a low-profile 28 GHz microstrip antenna on a polyimide substrate with varying Hs using CST Studio software. The simulated results and MINITAB software were used to develop regression model equations, which analyzed the impact of Hs variation on the antenna performance. The proposed models’ equations have indicated an increase in average responses of resonant frequency (Fr), percentage bandwidth (% BW), gain (G), return loss (RL), and efficiency (ƞ) as the Hs decreased. The antenna achieved a BW of 3.87 GHz at Hs 0.525 mm and 5.54 GHz at 0.025 mm, a G of 3.89 dBi at Hs 0.525 mm and 3.91 dBi at Hs 0.025 mm, and an ƞ of 94.19% at Hs 0.525 mm and 98.24% at Hs 0.025 mm. The antenna was fabricated and tested, and the experimental results were validated with the models’ equations. The thinner substrate resulted in an improvement in the antenna performance.